Influence of Split Application of Potassium on Yield and Yield Contributing Characters of rice cultivars- BR11 and Nizersail - Mahfuza, SN; Islam, MN; Aktar, Shamima; Amin, MR; Islam, MA (The Agriculturists, 2010)
Influence of split application of K on the sterility of BR11 and Nizersail was investigated in a field experiment conducted at the Bangladesh Agricultural University farm, Mymensingh during T. Aman season of 2003. The two rice varieties BR11 and Nizersail were grown with potassium applied at 70 kg and 60 kg K/ha, respectively. Split application of K showed similar effect of increasing trend in all the crop characters with the increase of the split applications from 1 to 3. Four splits were inferior to all. Three split of potassium showed superiority over 2, 1and 4 splits in almost all the crop characters, where the performance of Nizersail seemed to be better except in respect of sterile spikelets, grain yield and harvest index, where the superiority of BR11 was observed.